Associations between affect and alcohol consumption in adults: an ecological momentary assessment study. (2nd January 2020) - Duif, Mira; Thewissen, Viviane; Wouters, Saskia; Lechner, Lilian; Jacobs, Nele
ABSTRACT: Background : Consuming alcohol for coping with negative affect (NA) or enhancing positive affect (PA) may lead to risky drinking patterns. Previous research has yielded mixed findings regarding these affective drinking associations. Objectives : To examine support for the self-medication and expectancy models of alcohol use in an adult community sample, by examining reciprocal associations between alcohol consumption and NA and PA within and between persons. Methods : During seven consecutive days, 162 adults from the community (109 female) reported their affective experiences and alcohol consumption, following a signal contingent ecological momentary assessment protocol on their smartphones. Results : Within-person daily NA preceding the first drinking event was associated with increased likelihood of same-day alcohol consumption. Within-person momentary NA was associated with a decrease in the amount of next-moment alcohol consumption. Within-person momentary PA was positively associated with likelihood of next-moment alcohol consumption. Between persons, levels of daily and momentary NA and PA were not associated with any index of alcohol consumption. The intercepts and slopes of NA were not significantly different before and after alcohol consumption. The intercept of PA was higher after alcohol consumption, whereas the slope of PA decreased after alcohol consumption. Conclusion : In the current sample affective drinking was a within-person process (i.e. persons were sensitive to their varying levels of affect). Some support was found for the self-medication and expectancy models. People may drink for coping with NA, but may also be at risk for developing affective drinking patterns in response to PA.